Unsteady computational study of novel biologically inspired offshore vertical axis wind turbine at different tip speed ratios: a two-dimensional study - Ashwindran, S. N.; Azizuddin, Abd Aziz; Oumer, A. N. (Universiti Malaysia Pahang, 2019)
The aim of this paper presents an unsteady numerical investigation of a novel biologically inspired vertical axis wind turbine for offshore regions of Malaysia. The proposed blade shape is a result of hybrid design inspired by maple seed and epilobium hirsutum. The simulation was conducted in 2D using the sliding mesh technique with non-conformal mesh spatial discretisation via FLUENT 16.2. A grid sensitivity study on mesh density and turbulent transport model indicated that fine mesh and medium converged well with trivial difference. SST and k-ω model presented stable behaviour and indicated good agreement. The proposed wind turbine was simulated at five different moderate tip speed ratios under the influence of freestream velocity U∞=8 m/s. The highest moment coefficient is generated at tip speed ratio λ=1.3, which is Cm=0.1886 with a stable positive moment coefficient after 480°. The proposed turbine responded well at λ=1.3 and λ=1.7 with power coefficient result of Cp=0.245 and Cp=0.262 respectively. The effect of wake and vorticity on the turbine at subjected tip speed ratios is studied. Wake regions induced by the leading edge of the aerofoil impacted the performance of the following blade. Due to the less wake effect trailed by the leading edge at λ=1.3, it generates higher moment than λ=1.7.